2016
DOI: 10.1038/ng.3726
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-suppressor genes that escape from X-inactivation contribute to cancer sex bias

Abstract: There is a striking and unexplained male predominance across many cancer types. A subset of X chromosome (chrX) genes can escape X-inactivation, which would protect females from complete functional loss by a single mutation. To identify putative “Escape from X-Inactivation Tumor Suppressor” (EXITS) genes, we compared somatic alterations from >4100 cancers across 21 tumor types for sex bias. Six of 783 non-pseudoautosomal region (PAR) chrX genes (ATRX, CNKSR2, DDX3X, KDM5C, KDM6A, and MAGEC3) more frequently ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
326
2
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(347 citation statements)
references
References 58 publications
12
326
2
7
Order By: Relevance
“…Thus, female cells with two KDM6A gene copies likely have 424 more functional reserves to compensate for downregulation or inactivation of KDM6A compared to male 425 cells carrying only a single copy. Consistent with the adverse prognostic relevance of low KDM6A 426 expression affecting predominately male AML patients in the present study, it was recently shown that in 427 females KDM6A and other tumor suppressor genes may escape from X-inactivation (37). Of note, both 428 our AML patients with relapse-specific KDM6A mutations were females, however, one of the two lost an 429 X-chromosome at relapse based on CNA analysis, consistent with a VAF for the KDM6A mutation of Author Manuscript Published OnlineFirst on DOI: 10.1158/1078-0432.CCR-17-2344 Running title: Evolution of CN-AML relapse as there is no control group of relapsed patients, who had not received induction therapy 448 including high-dose cytarabine.…”
supporting
confidence: 89%
“…Thus, female cells with two KDM6A gene copies likely have 424 more functional reserves to compensate for downregulation or inactivation of KDM6A compared to male 425 cells carrying only a single copy. Consistent with the adverse prognostic relevance of low KDM6A 426 expression affecting predominately male AML patients in the present study, it was recently shown that in 427 females KDM6A and other tumor suppressor genes may escape from X-inactivation (37). Of note, both 428 our AML patients with relapse-specific KDM6A mutations were females, however, one of the two lost an 429 X-chromosome at relapse based on CNA analysis, consistent with a VAF for the KDM6A mutation of Author Manuscript Published OnlineFirst on DOI: 10.1158/1078-0432.CCR-17-2344 Running title: Evolution of CN-AML relapse as there is no control group of relapsed patients, who had not received induction therapy 448 including high-dose cytarabine.…”
supporting
confidence: 89%
“…A genomic basis for these differences is in the occurrence of somatic mutations on the sex chromosomes [7]. Of the six genes for which a sex bias was found in different tumor entities [7], only DDX2X had been reported previously in the context of poor risk CLL and clonal evolution [30, 31], Considering, however, the importance of sex steroids and gonadotropins for development and function of the immune system [6], we decided to focus our study on hormones and hormone metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…DDX3 mutations were identified in several cancer types[38], among which medulloblastomas[39], head and neck squamous cell carcinomas (HNSCC)[40], and hematological malignancies[4143]. In medulloblastomas, 50% of the Wnt subtype and 11% of the SHH subgroup tumors have a DDX3 mutation.…”
Section: Role Of Dead/h Box Proteins In Translating the Cancer Genomementioning
confidence: 99%